2017
DOI: 10.1186/s12957-016-1075-2
|View full text |Cite
|
Sign up to set email alerts
|

A single-institutional review of 68 patients with dermatofibrosarcoma protuberans: wide re-excision after inadequate previous surgery results in a high rate of local control

Abstract: BackgroundDermatofibrosarcoma protuberans (DFSP) is a cutaneous soft tissue sarcoma characterized by an indolent but aggressive local growth. Unplanned excisions with positive margins are common, and the prognostic impact of radical re-excisions is still unclear. The aim of the present study was to identify prognostic indicators of recurrence-free survival (RFS) in patients with DFSP through a long-term follow-up. We tried particularly to determine the prognostic impact of surgical margins and re-excisions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
(53 reference statements)
2
24
0
1
Order By: Relevance
“…Consequently, we would advocate using a margin width of at least 2 cm and scrupulous histopathological examination with re-excision upon close (R0) margins to achieve adequate results. This finding concurs with the recommendations of Harati et al 19 who also suggest 2-3-cm margins, as well as with the National Comprehensive Cancer Network (NCCN) Guidelines. Achieving adequate resection margins is key since recurrence is linked to positive margins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, we would advocate using a margin width of at least 2 cm and scrupulous histopathological examination with re-excision upon close (R0) margins to achieve adequate results. This finding concurs with the recommendations of Harati et al 19 who also suggest 2-3-cm margins, as well as with the National Comprehensive Cancer Network (NCCN) Guidelines. Achieving adequate resection margins is key since recurrence is linked to positive margins.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, complex or large tumors may be resectable only or in combination with wide excision. 15,[19][20][21] MMS was not applied at our institution. In our study, however, 12 out of 20 patients required plastic reconstruction due to large defects caused by excision with safety margins of 1-3 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies of our institution which have determined the influence of negative margin widths in STS, in general, could not establish a relationship between margin widths and outcome [24,25]. However, analyses of STS subsets such as angiosarcoma and dermatofibrosarcoma protuberans revealed that margin widths may indeed have an impact on specific entities [26][27][28]. Therefore, it is crucial to analyze the entities separately and to assess the prognostic significance of treatment-related factors for every histologic subset specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al represented a remarkable higher rate of DFSP recurrence in MMS using a frozen section as compared to sections embedded in paraffin. This may have occurred due to the changes in frozen dermal tissue, as the residues are difficult to be differentiated from the healthy dermal tissue, particularly following tissue freezing that would change the dermal architecture . Other factors that are affecting the frozen section include the tumor infiltration to the healthy dermis that may be mistakenly misdiagnosed with granulations formed secondary to the biopsies.…”
Section: Discussionmentioning
confidence: 99%